2008
DOI: 10.1002/jctb.1875
|View full text |Cite
|
Sign up to set email alerts
|

Production of organic solvent tolerant lipase by Staphylococcus caseolyticus EX17 using raw glycerol as substrate

Abstract: BACKGROUND: In this work we used Plackett-Burman statistical design and central composite design in order to optimize culture conditions for lipase production by Staphylococcus caseolyticus strain EX17 growing on raw glycerol, which was obtained as a by-product of the enzymatic synthesis of biodiesel. The stability of lipase was verified over several organic solvents, such as methanol, ethanol and n-hexane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 29 publications
1
34
1
Order By: Relevance
“…High levels of lipase production were reported from various microorganisms in the presence of olive oil as carbon source (Ahmed et al 2010;Balan et al 2013;Burkert et al 2004;Gupta et al 2007;Mehta et al 2012;Zaliha et al 2006). Most published experimental data have shown that lipid carbon sources especially natural oils stimulate lipase production, whereas carbon sources that are easily broken down and used by bacteria, have an inhibitory effect and contradict the results obtained by many studies (Burkert et al 2004;Gupta et al 2007;Volpato et al 2008;Zaliha et al 2006). In this study, lipase production enhancement was observed by addition of glucose at low concentration (0.5 %) and 1 % concentration of disaccharides, which could be due to enhanced growth of the bacterium and probably excretion of lipase was directly related to biomass production.…”
Section: Preliminary Optimization Using "One-variable-at-a-time"mentioning
confidence: 85%
“…High levels of lipase production were reported from various microorganisms in the presence of olive oil as carbon source (Ahmed et al 2010;Balan et al 2013;Burkert et al 2004;Gupta et al 2007;Mehta et al 2012;Zaliha et al 2006). Most published experimental data have shown that lipid carbon sources especially natural oils stimulate lipase production, whereas carbon sources that are easily broken down and used by bacteria, have an inhibitory effect and contradict the results obtained by many studies (Burkert et al 2004;Gupta et al 2007;Volpato et al 2008;Zaliha et al 2006). In this study, lipase production enhancement was observed by addition of glucose at low concentration (0.5 %) and 1 % concentration of disaccharides, which could be due to enhanced growth of the bacterium and probably excretion of lipase was directly related to biomass production.…”
Section: Preliminary Optimization Using "One-variable-at-a-time"mentioning
confidence: 85%
“…Studies by Rech (2010) using Staphylococcus warneri and glycerol as a carbon source showed excellent results regarding enzymatic activity. Volpato et al (2008) also obtained satisfactory lipase production results with Staphylococcus caseolyticus EX17 growing on crude glycerol obtained from biodiesel synthesis. Colla et al (2010) made a comparative study of lipase production by submerged fermentation and solidstate fermentation using Aspergillus sp.…”
Section: Lipase Productionmentioning
confidence: 85%
“…NBRC3259 could produce glyceric acid (49.5 g/L) and 28.2 g/L dihydroxyacetone from 174 g/L of CG [125]. Solvent tolerant lipase from CG was found to be produced by Staphylococcus caseolyticus EX17 [126]. Ustilago maydis was able to convert CG to glycolipid-type biosurfactants [127].…”
Section: Other Bioproductsmentioning
confidence: 99%